KEBIJAKAN HUKUM TERHADAP PELAKSANAAN PENGAMPUNAN PAJAK (TAX AMNESTY) DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT BANGSA INDONESIA (Jurnal Hukum Mimbar Justitia, 2017)
Tax amnesty is often used as a media in gathering state revenues from the tax sectors ina relatively short period of time. This program is implemented because of the taxworsening evasion effort. This policy create benefits funds, especially the returning ofoverseas deposits, and this policy has long term bad effect. The voluntary compliancefrom taxpayers decrease, when tax amnesty is implemented inappropriately, and givesan idea that the implementation of tax amnesty in some countries is relatively successfulin implementing tax forgiveness. This paper analyzes the factors that caused the successand achieves the targets in realizing the welfare for the Indonesian community.Keywords: Policy; Tax Amnesty; State Revenue; Voluntary Compliance; Public welfare